Standardization of 68Ge-68Ga using 4πβ(LS)-γ coincidence counting system for activity measurements. (May 2017) - Kulkarni, D.B.; Joseph, Leena; Anuradha, R.; Kulkarni, M.S.; Tomar, B.S.
Abstract: 68 Ga has great scope for use in future for positron emission tomography (PET) imaging due to its very fast blood clearance and fast target localization, even though at present 18 F is widely used. 68 Ge in equilibrium with 68 Ga ( 68 Ge- 68 Ga) can also be used as a surrogate for 18 F calibration, as 18 F source standardization can be done at national metrology institute (NMI) but, these standards cannot be sent to nuclear medicine centers (NMCs) across India for calibration of isotope calibrators, due to the short half-life of 18 F (110 min). Providing 68 Ge- 68 Ga standards to NMCs requires that first standardization must be carried out at NMI (BARC in India) to provide traceability to the measurements carried out at NMCs. In the present work, standardization of 68 Ge- 68 Ga was carried out using 4πβ(LS)-γ coincidence counting system and CIEMAT/NIST efficiency tracing technique. The decay scheme correction factors for two gamma windows were calculated by Monte Carlo technique using general purpose code FLUKA. The activity concentration values were normalized by the activity concentration obtained by 4πβ(LS)-γ coincidence counting system using window-1. The final result reported to BIPM for 4πβ(LS)-γ coincidence counting was calculated by taking arithmetic mean of activity concentrations obtained for two gamma windows. The normalized activity concentration obtained by 4πβ(LS)-γ coincidence counting was 0.998±0.005 and that obtained using CIEMAT/NIST efficiency tracing was 1.002±0.007 which are in excellent agreement within uncertainty limits. Highlights: Standardization of 68 Ge in equilibrium with 68 Ga carried out using 4πβ(LS)-γ system. Decay scheme correction factor evaluated by Monte Carlo method. Activity concentration by 4πβ(LS)-γ and CIEMAT/NIST methods compared. Traceability for 4π-γ ion chamber (secondary standard) measurement established.